PS 17-77 A RANDOMIZED, DOUBLE-BLIND AND DOUBLE-DUMMY, MULTIPLE-DOSE, POSITIVE AND PARALLEL COMPARATIVE, MULTICENTER CLINICAL TRIAL OF ALLISARTAN EVALUATE EFFICACY AND SAFETY IN PATIENTS WITH MILD TO MODERATE ESSENTIAL HYPERTENSION. (September 2016) - Ma, Zhiyi; Wang, Hongyi; Jing, Shan; Chen, Yuanyuan; Xi, Yang; Ma, Qingchun; Lu, Xining; Sun, Ningling
Abstract : Objective: The objective of the study was to evaluate the efficacy, safety and tolerability of 3 dose regimens (80 mg, 160 mg or 240 mg qd) of allisartan in patients with mild to moderate essential hypertension. Design and method: The trial was designed as a multicenter, randomized, double-blind and double-dummy, positive and parallel comparative, dose-ranging study to evaluate the efficacy and safety of allisartan compared to losartan after 8 weeks treatment in patients with essential hypertension (90mmHg ⩽ msDBP < 110 mmHg and 140 mmHg ⩽msSBP < 180 mmHg). The trial enrolled 283 subjects. After 2 weeks of placebo run-in period, subjects were randomized to Allisartan 80 mg group, Allisartan 160 mg group, Allisartan 240 mg group or Losartan 50 mg group by1:1:1:1, who were treated for 8 weeks. Results: There were 279 subjects in full analysis set. Efficacy result: Mean sitting diastolic blood pressure (msDBP) and systolic blood pressure(msSBP) of the four groups were reduced significantly after 8 weeks. There were no differences on the decrease of blood pressure among four groups, the P value of msSBP and msDBP was 0.3706 and 0.2626. There were no differences on the proportion of patients achieving msSBP and msDBP responses (< 140 mmHg or a reduction of ≥ 20 mmHg from baseline; and < 90 mmHg or a reduction ≥ 10 mmHg from baseline) among four groups, the P value was 0.3252. Safety results:No SAE was reported. The overall incidence of adverse events was low during the study. The most commonly reported AEs were dizzy, headache, nausea and abnormal liver function. There were no differences on AEs among four groups, the P value was 0.5939. Conclusions: The study showed that all 3 doses of allisartan were efficacious and safe in treating Chinese patients with essential hypertension. Allisartan can reduce systolic and diastolic blood pressure significantly. Allisartan is well tolerated and has better safety.